From Boleas to Bangui: Parliamentary oversight of South African defence deployments - Janse van Rensburg, Wilhelm; Vreÿ, Francois; Neethling, Theo (Scientia Militaria - South African Journal of Military Studies, 2020)
Parliamentary oversight of the executive plays a key role in ensuring accountability and is therefore central to the system of checks and balances that characterises liberal democracies. After 1994, South Africa aligned itself with liberal democratic ideals and sought to foster accountability in governance. In the South African Parliament, committees are considered the engine rooms of the institution and are central to the oversight process. Members of Parliament serving on these committees also have specific tools at its disposal to conduct oversight. These include deliberations (debates), posing written and oral questions, oversight visits, special inquiries and external audit opinions. By reviewing the use of these tools in relation to defence deployments, this article aims to determine the long-term post-1994 trajectory of parliamentary oversight of deployments. The article uses the timeline between Operation Boleas (Lesotho, 1998) and the ‘Battle of Bangui’ (Central African Republic, 2013), two key post-1994 military deployments, as a demarcation for determining the trajectory of oversight. The article finds a negative trajectory in terms of the oversight of deployments. Committee meetings dedicated to deployments remained limited. Questions around deployments did not fill the vacuum left by a lack of committee activity. Oversight visits to deployment areas were limited while there was a complete dearth of in-depth inquiry into deployments through special inquiries and external audits. The article subsequently notes that the negative trajectory in terms of deployment oversight can not only be explained by the growing civil-military gap in South Africa, but arguably contributed to the widening gap.